Patent-Ineligibility as Counteraction - Kevin E. Collins (Washington University Law Review, 2017)
Today, normative debates over restrictions on patent-eligibility are uniformly premised on a discrimination theory of patent-ineligibility: the restrictions are assumed to cause the patent regime as a whole to discriminate against, and thus grant weaker patent protection for, the affected technology. Under discrimination theory, the justification for a rule of patent ineligibility turns on whether there is a good reason to treat the affected technology differently and grant it only relatively weak protection. In contrast, this Article articulates a novel counteraction theory of patent- ineligibility. Counteraction theory adopts the default premise that all technologies merit roughly the same strength of patent protection, and it recognizes that, in some circumstances, a well-tailored restriction on patent-eligibility can be the most effective means of achieving that rough equality. The weakening of patent protection caused by restrictions on patent-eligibility can sometimes offset the unusually strong protection that is created by inherent, technology-specific biases in the patent doctrines other than patent-eligibility, including novelty, nonobviousness, and enablement. A restriction on the patent-eligibility of a technology can thus bring the strength of the patent protection available for the technology back closer to the norm of protection granted for all technologies. A full account of counteraction theory entails an explanation of when and how the inherent, technology-specific biases in favor of strong protection can arise in the patent doctrines other than patent-eligibility, such as novelty, nonobviousness, and enablement. This Article focuses on one such explanation: the dematerialization of technology in today’s knowledge-age economy has led to technology-specific regulatory inefficacy in these doctrines. Certain non-eligibility patent doctrines cannot do the work of regulating patent validity that we expect them to be able to do when they are brought to bear on certain intangible technologies, meaning that they sanction unusually strong protection for those technologies. Technology-specific regulatory inefficacy sets the stage for a counteraction-oriented justification of restrictions on patent-eligibility. The restrictions can counteract or neutralize the unusually strong protection created by the inefficacy of the non-eligibility doctrines, bringing the strength of the patent protection that is available for the affected technology back into closer alignment with the protection that is available for other technologies. In addition to articulating counteraction theory and technology-specific regulatory inefficacy as theoretical possibilities, this Article examines the actual restrictions on patent-eligibility in two intangible technologies that are on the front lines of the ongoing battles over patent-eligible subject matter: diagnostic inferences and software. The Supreme Court has recently announced restrictions on the patent-eligibility of both technologies, and both restrictions are highly controversial under discrimination theory. However, the restrictions have a reasonable, although concededly imperfect, fit with the restrictions that can be justified under counteraction theory. In each technology, patent protection is unusually strong because certain non-eligibility doctrines fail to provide their expected validity- limiting regulation, and the Court’s restriction on patent-eligibility works to counteract that strength.
Keywords: PATENT-INELIGIBILITY; patent-eligibility; discrimination theory; Counteraction theory; technology-specific; regulatory inefficacy; Bilski v. Kappos; 561 U.S. 593 (2010); Alice Corp. v. CLS Bank Int’l; 134 S. Ct. 2347 (2014); Mayo Collaborative Servs. v. Prometheus Labs.; Inc.; 132 S. Ct. 1289 (2012); Ass’n for Molecular Pathology v. Myriad Genetics; 133 S. Ct. 2107 (2013)